A highly selective chromogenic and fluorogenic chemodosimeter for dual detection of Cu2+ based on a redox-active calix[4]arene with isoxazolylchloroanthracene. Issue 22 (11th October 2022) - Chang, Kai-Chi; Chen, Chan-Yu; Hsu, Chin-Yun; Lee, Li-Wei; Chung, Wen-Sheng
Abstract : Calix[4]arene 1 with 25, 27-diisoxazolylchloroanthryl groups is a chromogenic and fluorogenic sensor for Cu 2+ with a LOD of 1.67 μM by fluorescence. Calix[4]diquinone was obtained in high yield through the redox reaction of ligand 1 with Cu(ClO4 )2 . Abstract : Calix[4]arene 1, with two lower-rim isoxazolylchloroanthracene groups, is shown to be not only a chromogenic but also a fluorogenic chemodosimeter for the selective sensing of Cu 2+ . The binding properties of ligand 1 and control compounds 2 and 3 toward metal ions in CH3 CN/CHCl3 (v/v, 1 : 1) were investigated by UV-vis and fluorescence spectroscopy. The results showed that only ligand 1 was highly selective for Cu 2+ ions. When complexed with Cu 2+, ligand 1 displayed a new absorption band around 435 nm and the color of the solution changed from colorless to yellow. Furthermore, the fluorescence of ligand 1 was severely quenched by Cu 2+ and the limit of detection (LOD) was determined to be 1.674 μM. Therefore, compound 1 is not only a chromogenic but also a fluorogenic sensor for the detection of Cu 2+ ions over other metal ions examined. When complexed with ligand 1, Cu 2+ was reduced to Cu + by the free phenolic-OH of ligand 1 and concurrently the phenol was oxidized by Cu 2+ to quinones. The 1 H NMR, EPR, and FTIR spectra provided evidence for the redox behavior of ligand 1 with Cu 2+ . The isolation of calix[4]diquinone 8 and Cu(CH3 CN)4 ClO4 from the reaction of ligand 1 with Cu(ClO4 )2 confirmed their redox reaction.